Performance of Costus speciosus Genotypes under Different Agro-Climatic Zones of Chhattisgarh - Kanwar, R R; Shankar, Deo; Singh, D P; Sahu, M K; Narayan, Kamal; Mukherjee, Deepanshu (JOURNAL OF ROOT CROPS, 2017)
An investigation was made through multi location trial (MLT) to evaluate the genotypes of Costus speciosus locally known as Kewkand under different agro-climatic zones of Chhattisgarh to identify the high rhizome yielding genotype. The experiment was conducted during Kharif 2014-15 and 2015-16 at ten locations under Chhattisgarh Northern Hill Region and Bastar Plateau of Chhattisgarh with four genotypes including local check. The locations were the replication in the experiment. The experiment was laid out in Randomized Complete Block Design (RCBD) with four treatments viz . IGKK-1, IGKK-3, IGKK-4 and Local check with ten replications viz . L 1 : Jagdalpur, L 2 : Kanker, L 3 : Narayanpur, L 4 : Dantewada, L 5 : Bijapur, L 6 : Balrampur, L 7 : Jashpur, L 8 : Surguja, L 9 : Korea & L 10 : Raigarh. The pooled data of two years revealed that the maximum plant height, number of leaves per plant, early maturity, number of rhizome per plant and average rhizome yield was recorded genotype IGKK-1. Among the four genotypes IGKK-1 gave significantly higher rhizome yield of 24.47 t ha -1 . The genotype IGKK-1 is the promising genotype for commercial cultivation in Chhattisgarh.